S100P Expression in response to sex steroids during the implantation window in human endometrium - Zhang Dan; Ma Chengbin; Sun Xiaoli; Xia Hexia; Zhang Wei (BMC, 2012)
Abstract Background S100P, a protein originally detected in the human placenta, has been found to play an important role in the development and invasion of tumors. Interestingly, we have recently discovered using data mining that S100P was considerably up-regulated during the window of implantation in the human endometrium, but little further information has been available. Methods Real-time PCR and immunofluorescence were performed to examine the expression and location of S100P in the human endometrium and endometrial cells. Estrogen and progesterone were added to the cultured cells to test the response of S100P to sex steroids. Results A dramatic peak, approximately a 100-fold increase in comparison with the proliferative and early- and late-secretory phases, was observed in the endometrium during the mid-secretory phase, which corresponds to the time of embryo implantation. Progesterone regulated the expression of S100P in both primary endometrial epithelial and stromal cells, but estrogen had no significant effect. Conclusions The results indicate that S100P participates in the periodic change of the endometrium under the regulation of progesterone, may be used as a unique biomarker of the receptive endometrium and play an important role in embryo implantation.